Activation of the receptor for advanced glycation end products induces nuclear inhibitor of protein phosphatase-1 suppression - Liebisch, Marita; Bondeva, Tzvetanka; Franke, Sybille; Daniel, Christoph; Amann, Kerstin Ute; Wolf, Gunter (Kidney International, 2014)
The activation of the receptor for advanced glycation end products (RAGE) is involved in the development of diabetic nephropathy. Analysis of protein phosphatase-1 indicated that advanced glycation end products did not affect its expression, but increased its phosphatase activity. Using differential display analysis we previously demonstrated that stimulation of RAGE in podocytes modulates the expression of numerous genes, among others nuclear inhibitor of protein phosphatase-1 (NIPP1). Here we found that silencing of NIPP1 induced podocyte hypertrophy, cell cycle arrest, and significantly increased protein phosphatase-1 activity. NIPP1 downregulation was associated with increased p27(Kip1) protein expression. Reporter assays revealed a transcriptional activation of nuclear factor-?B in podocytes after suppression of NIPP1. The protein level of NIPP1 was also significantly reduced in podocytes of diabetic mice. Blocking the RAGE in vivo by a soluble analog elevated the NIPP1 protein in podocytes of diabetic mice. Thus, activation of the RAGE by advanced glycation end products or other ligands suppresses NIPP1 expression in diabetic nephropathy, contributes to podocyte hypertrophy, and glomerular inflammation.
EVALuna2:25459